Aquaculture en système clos : estimation des coûts de production pour l'élevage du bar et du turbot - Lavenant, M; Paquotte, Philippe (Communication au séminaire SELAM, sur les aspects économiques de l'aquaculture en Méditerranée, CIHEAM / IFREMER Montpellier 17-19 mai 1995, 1995)
Two major constraints to aquaculture have raised in most countries : the little availability of convenient sites because of the competition for the use of the coastline and the progressive implementation of regulations to reduce the impact of the farms on the environment. The technique of recirculation, widely used for hatcheries, has been developed to answer these constraints and to get free of the natural variations in order to regulate the résults. The ongrowing experimental facilities have proved good enough results to make it possible to conceive industrial projects for sea-bass and turbot. In first approach, the production costs of these systems are similar to traditional techniques but expected productivity gains due to an increase of zootechnical results in controlled environment and to technological improvements are important. The possibility to control all the parameters makes it possible to rear other faster-growing species. These•systems have the advantage to be less polluting because of the continuous internal treatment of the water and of the elimination of most dissolved nitrogen. Concentrated wastes treatment becomes more affordable both technically and financially. All these results and perspectives will certainly give a bright future to this technique for intensive fish farming. [NOT CONTROLLED OCR] Deux contraintes majeures au développement de l'aquaculture sont apparues dans la plupart des pays : la très faible disponibilité en sites propices à l'installation d'entreprises à cause de la forte compétition pour l'usage du littoral, et la mise en place progressive de réglementations pour limiter l'impact des élevages sur le milieu naturel. La technique d'aquaculture en système clos ou circuit fermé, par ailleurs largement utilisée en écloserie-nurserie, a été mise au point d'une part, pour répondre à ces contraintes et d'autre part, pour s'affranchir des variations naturelles des conditions du milieu extérieur et tenter d'uniformiser les paramètres et donc les résultats d'élevage. Les ...